Tradycyjne i nowe argumenty protekcjonizmu handlowego na przykładzie Wspólnoty Europejskiej - Puślecki, Zdzisław W. (Wydział Prawa i Administracji UAM, 1992)
Article presents traditional and new theoretical justifications of trade prtektjonism on theexample of the European Community. Besides traditional arguments for trade protectionism, such as the improvement of terms of trade, protection of infant industry, protection of balance of payments, protection of income and employment, new arguments appear, namely the argument referring to excessive dependence of domestic economy on import and the argument referring to unfavorable influence of excessive exposure to foreign countries on macroeconomic stability of economy. The leading argument of the contemporary trade protectionism, also in the EEC countries, is the protection of income and employment. Since protectionism is costly, it should be applied on a temporary basis only. Extended trade protectionism leads to the petrification of obsolete economic structures and weakens the economic efficiency.
Tradition and new arguments for trade protectonism (on the example of the EEC)